Decoding nature: multi-target anti-inflammatory mechanisms of natural products in the TLR4/NF-κB pathway - Zhao, Yue; Wu, Jiacai; Liu, Xiaolan; Chen, Xu; Wang, Juan (Frontiers in Pharmacology, 2025)
Natural products are valuable medicinal resources in the field of anti-inflammation due to their significant bioactivity and low antibiotic resistance. Research has demonstrated that many natural products exert notable anti-inflammatory effects by modulating the Toll-like receptor 4 (TLR4) and nuclear factor kappa B (NF-κB) signaling pathways. The research on related signal transduction mechanisms and pharmacological mechanisms is increasingly being discovered and validated. However, there is currently a lack of comprehensive reviews focusing on the pharmacological mechanisms of natural products targeting the TLR4/NF-κB pathway for anti-inflammatory effects. In light of these considerations, this review comprehensively synthesizes recent research findings concerning the TLR4/NF-κB signaling pathway, including the translocation of TLR4 activation to lysosomes within the cytoplasm, the assembly of protein complexes mediated by ubiquitin chains K63 and K48, and the deacetylation modification of p65. These discoveries are integrated into the classical TLR4/NF-κB pathway to systematically elucidate the latest mechanisms among various targets. Additionally, we summarize the pharmacological mechanisms by which natural products exert anti-inflammatory effects through the TLR4/NF-κB pathway. This aims to elucidate the multitarget advantages of natural products in the treatment of inflammation and their potential applications, thereby providing theoretical support for molecular pharmacology research on inflammation and the development of novel natural anti-inflammatory drugs.